Advances in Cellular Characterization of the Sirtuin Isoform, SIRT7 - Wu, Di; Li, Yinglu; Zhu, Kathy S.; Wang, Haiying; Zhu, Wei-Guo (Frontiers in Endocrinology, 2018)
SIRT7 is one of seven mammalian sirtuins that functions as an NAD+-dependent histone/protein deacetylase. SIRT7 is the least well-known member of the sirtuin family, but recent efforts have identified its involvement in various cellular processes, such as ribosome biogenesis, gene expression, cellular metabolism and cancer. Here we provide an update on the functions and mechanisms of SIRT7 in cellular regulation and disease.